2008
DOI: 10.3748/wjg.14.2162
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NHE1 antisense gene transfection on the biological behavior of SGC-7901 human gastric carcinoma cells

Abstract: AIM:To study the effect of type 1 Na + /H + exchanger (NHE1 ) antisense human gene transfection on the biological behavior of gastric carcinoma cell line SGC-7901. METHODS:Antisense NHE1 eukaryotic expression on vector pcDNA3.1 was constructed by recombinant DNA technique and transfected into gastric carcinoma cell line SGC-7901 with DOTAP liposome transfection method.Morphological changes of cells were observed with optic and electron microscopes. Changes in cell proliferative capacity, apoptosis, intracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2009
2009
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…Our findings were supported by others. Liu 35 showed that the NHE1 antisense gene significantly suppressed cell proliferation and cell cycle of gastric carcinoma cell line SGC‐7901. Perez‐Sala 21 reported that the activation of the NHE1 suppressed apoptosis of HL‐60 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were supported by others. Liu 35 showed that the NHE1 antisense gene significantly suppressed cell proliferation and cell cycle of gastric carcinoma cell line SGC‐7901. Perez‐Sala 21 reported that the activation of the NHE1 suppressed apoptosis of HL‐60 cells.…”
Section: Discussionmentioning
confidence: 99%
“…These data support that decrease in NHE1 expression can be specifically induced in tumor cells overexpressing PPARγ, leaving normal cells unaffected. In light of the recent study showing that an antisense therapy targeting NHE1 gene in gastric cancer decreased invasive capacity, and loss of cloning efficiency, and tumorigenicity in nude mice (43), the repressive effect of PPARγ activation on NHE1 expression presents a window of opportunity for exploiting PPARγ agonists for selectively tailoring the expression of NHE1 to achieve a favorable therapeutic response. In addition, synergy between rosiglitazone and platinum-based drugs in several different cancers both in vitro and using transplantable and chemically induced "spontaneous" tumor models was recently reported (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…• Gastric cancer Paehler Vor der Nolte et al, 2017 Xue et al, 2011Czepán et al, 2012Liu et al, 2008He et al, 2010;Nagata et al, 2011;Hosogi et al, 2012;Xia et al, 2016;Xie et al, 2017 NHE1 Intestine…”
Section: The Role Of Nhe1 In Barrett's Esophagus and Its Progression unclassified